1995
DOI: 10.1002/spe.4380251004
|View full text |Cite
|
Sign up to set email alerts
|

A tool for visualizing the execution of interactions on a loosely‐coupled distributed system

Abstract: The paper describes in detail the implementation of INMON, a prototype monitor for recording and displaying interaction networks. The interaction network is designed to show the interrelationships between significant events that occur during the processing of an interaction on a loosely‐coupled distributed system. By being directed at analysing what happens in an interaction, this approach is fundamentally different from other graphical representations that show what happens during the execution of a single pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Interaction network monitors are not MINIX-specific, and can be applied to a wide variety of message based systems, as shown by previous implementations for SunOS [2] and Amoeba [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction network monitors are not MINIX-specific, and can be applied to a wide variety of message based systems, as shown by previous implementations for SunOS [2] and Amoeba [1].…”
Section: Discussionmentioning
confidence: 99%
“…A strength of the interaction network is that it captures all server processing required to carry out a user request. Although interaction networks were developed originally to support performance measurement, experience with interaction network monitors developed for SunOS [2] and Amoeba [1] showed that displays of interaction networks gave considerable insights into the behaviour of message passing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ashton and Penny [8] developed INMON, an "interaction network monitor" for distributed systems. INMON is designed to follow the flow of control as it passes from process to process, kernel to kernel, and machine to machine in response to individual user actions.…”
Section: System Call Tracingmentioning
confidence: 99%